2015
DOI: 10.5194/acp-15-8577-2015
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in global aerosols and climate effects due to biofuel emissions

Abstract: Abstract. Aerosol emissions from biofuel combustion impact both health and climate; however, while reducing emissions through improvements to combustion technologies will improve health, the net effect on climate is largely unconstrained. In this study, we examine sensitivities in global aerosol concentration, direct radiative climate effect, and cloud-albedo aerosol indirect climate effect to uncertainties in biofuel emission factors, optical mixing state, and model nucleation and background secondary organic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 75 publications
(98 reference statements)
6
88
2
Order By: Relevance
“…Downwind of source regions, N 3 concentrations are reduced by up to ∼ 400 cm −3 . This reduction is caused by primary particles acting as a coagulation sink for nucleated particles and a condensation sink for nucleating and condensing vapours, suppressing new particle formation (Spracklen et al, 2006), which is broadly consistent with the findings of Kodros et al (2015) for particle number concentrations due to the effect of biofuel emissions.…”
Section: Impact Of Residential Emissions On Total Particlesupporting
confidence: 78%
See 4 more Smart Citations
“…Downwind of source regions, N 3 concentrations are reduced by up to ∼ 400 cm −3 . This reduction is caused by primary particles acting as a coagulation sink for nucleated particles and a condensation sink for nucleating and condensing vapours, suppressing new particle formation (Spracklen et al, 2006), which is broadly consistent with the findings of Kodros et al (2015) for particle number concentrations due to the effect of biofuel emissions.…”
Section: Impact Of Residential Emissions On Total Particlesupporting
confidence: 78%
“…The review of Bond et al (2013) identified a net negative RE (DRE and AIE) for biofuel with large uncertainty but a slight net positive RE (with low certainty) from residential coal (Bond et al, 2013). However, a recent detailed global modelling study found that the climate effects of residential biofuel combustion aerosol are largely unconstrained because of uncertainties in emission mass flux, emitted size distribution, optical mixing state, and ratio of BC to POM (Kodros et al, 2015) In addition to impacting climate, aerosol from residential fuel combustion degrades air quality with adverse implications for human health. Epidemiologic research has confirmed a strong link between exposure to particulate matter (PM) and adverse health effects, including premature mortality (Pope III and Dockery, 2006;Brook et al, 2010).…”
Section: E W Butt Et Al: the Impact Of Residential Combustion Emismentioning
confidence: 99%
See 3 more Smart Citations